Some science scholars their identification and experiential background - Elequin, Eleanor (Education quarterly.)
The National Science Development Board has outlined a broad program of activities which include a nation-wide talent search, a summer institute for science teachers, a graduate student course and specialized training for atomic technicians. This paper is an outgrowth of the science talent search, a jointly activity of the Science Foundation of the Philippines and the Board of National Education. The exploratory character of the identification of science scholars must be emphasized. it merely presents the results of an inquiry into items which seem related to educational and vocational behavior of the science scholars.